A STUDY ON IMPACT OF ORGANIC FOOD PRODUCTS TOWARDS THE BUYING BEHAVIOUR OF CONSUMERS IN KANYAKUMARI DISTRICT - G. Suganthi Priya; S. Mahadevi.S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Organic food products significantly impact consumer buying behavior by shaping preferences, priorities, and purchasing decisions. Health consciousness is one of the primary factors driving this behavior. Many consumers perceive organic foods as healthier alternatives, free from synthetic chemicals, pesticides, and genetically modified organisms (GMOs). This perception influences health-focused buyers to prioritize organic options, particularly for fresh produce, dairy, and meat products. For families, especially those with young children, organic food is often seen as a safer and more nutritious choice, encouraging them to spend more on organic groceries despite higher costs. In addition to health benefits, sustainability and ethical considerations heavily influence consumer buying behavior. Increasing awareness about environmental issues has made eco-conscious consumers more inclined to choose organic foods, which are produced using environmentally friendly farming practices. Ethical considerations, such as support for fair trade and local farming communities, further strengthen the bond between organic food brands and socially responsible buyers, fostering brand loyalty. The important objective of this study is analyze the impact of organic food products towards the buying behaviour of consumers in Kanyakumari district. The study is confined with both primary and secondary data. In order to study the impact of organic food products towards the buying behaviour of consumers in Kanyakumari district 50 consumers of organic food products are randomly selected as samples using convenient sampling method. The collected data were analyzed with the help of various statistical measures such as Percentage, Friedman test and Chi-Square Test.